Aplicaciones tecnológicas de la dosificadora y selladora de fundas para fluidos en procesos de transformación Agroindustrial. - Castellano Porras, Jefferson Marcelo (2023)
The purpose of this titration project is to present the operation, maintenance of the dosing machine and fluid sleeve sealer in the Agro-industry career research laboratory, strengthening the technical knowledge of operators and personnel who wish to manipulate the equipment, in a generation of new knowledge and research. It is carried out, based on exploratory, descriptive and explanatory research applied in the information summary. To obtain, a manual that describes the characteristics, safety measures and specific parts that is formed for its routine operation and maintenance, preventive, predictive and corrective that must be executed to extend the useful life of the equipment. As a result, the study of the technological applications of said machine, provides valuable information for the agro-industrial sector, through the realization of laboratory practices was determined to improve productivity, reduces manual labor and ensures a quality sheathed product.